1985
DOI: 10.1159/000176968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Cholesterol and Cholestyramine on Developmental Pattern of 3-Hydroxy-3-Methylglutaryl-CoA Reductase

Abstract: Supplementation of the diet with 2% cholesterol suppressed the increase observed in the hepatic and intestinal 3-hydroxy-3-methylglutaryl-CoA reductase activity from normally fed chicks during the first days after hatching. Cholestyramine feeding clearly increased both hepatic and intestinal reductase activities. In contrast, brain reductase did not show significant changes by cholesterol or choelstyramine feeding. Dietary cholesterol produced a clear increase in the cholesterol/lipidic phosphorus molar ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…29,38 This high level was also maintained during further development (21-28 days). 41 A similar inhibition of reductase activity by cholesterol feeding also was observed in chick intestine 40 and in isolated enterocytes from chick duodenum, jejunum, and ileum, 42 although in this tissue differences between peak and nadir values were always smaller than those observed in liver. 43 The hypercholesterolemic effect of cholesterol was generally accompanied by the accumulation of cholesterol in liver, thus interfering with the hepatic cholesterogenesis.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…29,38 This high level was also maintained during further development (21-28 days). 41 A similar inhibition of reductase activity by cholesterol feeding also was observed in chick intestine 40 and in isolated enterocytes from chick duodenum, jejunum, and ileum, 42 although in this tissue differences between peak and nadir values were always smaller than those observed in liver. 43 The hypercholesterolemic effect of cholesterol was generally accompanied by the accumulation of cholesterol in liver, thus interfering with the hepatic cholesterogenesis.…”
Section: Discussionsupporting
confidence: 66%
“…39 On the other hand, the clear inhibition of HMG-CoA reductase activity induced by coconut oil plus cholesterol feeding is in agreement with that previously observed in neonatal chicks that were fed a diet supplemented with 2% cholesterol during the 2 first weeks after hatching. 40 This inhibition was found when animals were euthanized approximately 12 hours after food deprivation, as in this work. Levels of HMG-CoA reductase activity in control chicks were practically similar to those observed in the present work.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Cholestyramine treatment results in hypocholesterolemia and in higher rates of cholesterol synthesis. Thus, in pre vious studies it has been demonstrated that both liver and intestinal HMG-CoA reduc tase of chicks fed 3% cholestyramine from hatching were increased with respect to con trols after 7 days of treatment [1]. The present results obtained in intestine consti tute, to our knowledge, the first report on the effect of cholestyramine on phosphorylation and decarboxylation of MVA in this organ.…”
Section: Discussionsupporting
confidence: 64%
“…We have also used chicks previously to study lipid metabolism after cholesterol administration (30)(31)(32)(33). The aim of this study was to develop a cell-culture avian model to look into the effect of a cholesterol diet on the transformation of SMC in vivo.…”
mentioning
confidence: 99%